2014
DOI: 10.5624/isd.2014.44.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vertical root fracture using cone-beam computed tomography

Abstract: PurposeThe aim of this study was to investigate the accuracy of cone-beam computed tomography (CBCT) in the diagnosis of vertical root fractures in a tooth with gutta-percha and prefabricated posts.Materials and MethodsThis study selected 96 extracted molar and premolar teeth of the mandible. These teeth were divided into six groups as follows: Groups A, B, and C consisted of teeth with vertical root fractures, and groups D, E, and F had teeth without vertical root fractures; groups A and D had teeth with gutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
1
20
1
2
Order By: Relevance
“…10 CBCT has allowed dental practitioners to visualize teeth three-dimensionally and with high spatial resolution. 11 While recent studies have demonstrated the superiority of CBCT in detecting root fractures, 1,3,4,6,[12][13][14][15] there are some limitations to proper imaging when high-density materials such as guttapercha and intracanal metal posts are present. These materials may create artefacts that impair the quality of CBCT images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 CBCT has allowed dental practitioners to visualize teeth three-dimensionally and with high spatial resolution. 11 While recent studies have demonstrated the superiority of CBCT in detecting root fractures, 1,3,4,6,[12][13][14][15] there are some limitations to proper imaging when high-density materials such as guttapercha and intracanal metal posts are present. These materials may create artefacts that impair the quality of CBCT images.…”
Section: Introductionmentioning
confidence: 99%
“…Beam hardening and streak artefacts can be superimposed on the root, creating difficulties for image assessment and may even mimic root fractures. 4,6,7,9,12,[15][16][17] Some specific tools can be used to analyse CBCT images, including filters that use mathematical algorithms to minimize image noise and improve image quality. 18,19 Some studies have shown that CBCT filters improve the diagnosis of root fractures in nonendodontically treated teeth, 5,19 but studies evaluating the influence of filters on the diagnosis of fractures in endodontically treated roots are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda, radyasyon dozu, görüntü kalitesi ve hasta rahatlığı açısından BT'ye göre daha avantajlı olan konik ışınlı bilgisayarlı tomografi (KIBT) tekniği öne çıkmıştır 3 . Bilgimiz dâhilinde, literatürde maksillofasiyal fraktürlerin KIBT ile değerlendirildiği az sayıda araştır-ma bulunmaktadır ve bu çalışmalarda genellikle dental fraktürler incelenmiştir 4,5 . Bu çalışmanın amacı, maksillofasiyal bölgedeki fraktürlerin radyografik özelliklerini KIBT ile retrospektif olarak değerlendirmektir.…”
Section: Gġrġġunclassified
“…Maksillofasiyal fraktürlerin KIBT ile değerlendirildiği çalışmalarda araştırmacılar genellikle dental fraktürlere odaklanmışlardır [4][5][6] . Bu konuda genellikle olgu sunumları, derlemeler, panoramik radyografi, BT ve KIBT'nin etkinliğinin karşılaştırıldığı ça-lışmalar yapılmıştır [7][8][9][10] .…”
Section: Tartiġmaunclassified
“…Beam hardening and streak artifacts can be superimposed on the root, creating difficulties for image assessment and may even mimic root fractures. [5,6] Recent CBCT machines can apply metal artifact reduction algorithms that may be effective in reducing metallic posts artifacts which will provide 3-dimensional CBCT images with metallic artifacts reduction and thus allow for better detection of root fractures in teeth with metallic posts. It was demonstrated that the artifact reduction algorithm in the Master 3D machine (Vatech, Hwaseong, South Korea) enhances the contrast-tonoise ratio of the resulting images.…”
Section: Introductionmentioning
confidence: 99%